Expanding the Rule of Law: Judicial Reform in Latin America - Linn Hammergren (Washington University Global Studies Law Review, 2005)
This article seeks to convey three main message concerning judicial reform in Latin America. First, over the past twenty years, reform formulas (or reform recommendations) have been implemented, to a large extent, in countries throughout the region. There are variations—one can argue about detail, one can even argue about whether the people who were implementing them really understood the purpose underneath the formula, but a lot has changed. Second, the change—which has been structural and procedural to a large extent—has not necessarily brought the improvements in performance or output that were promised. At this point, those who have been promoting these reforms must ask whether the result toward which these countries are headed is really where they want to be. There may be some tendencies we are promoting that are not wellconsidered. The third message is that it is time for a change in direction.
Keywords: Judicial process; Rule of law; Central America; South America